The Influence of Hedonic and Utilitarian Engagement in Generation Z on Continued Use of the Spotify App - Muhammad Firdaus; Anas Hidayat (Indonesian Journal of Economics, Business, Accounting, and Management (IJEBAM), 2024)
The massive growth of social media has kept generation z updated. Spotify created spotify recap which increased the number of downloads and listeners. This study aims to determine the effect of hedonic involvement and utilitarian involvement on application attitudes and sustainable application use aimed at generation z (1997-2012). Primary data with 200 respondents. Using non probability sampling technique with convencience sampling method. Hypothesis testing using Structural Equation Modeling - Partial Least Square method with Smart-PLS application. The results concluded that hedonic engagement and utilitarian engagement are proven to have a positive and significant influence on application attitudes and continued application use. In addition, this study also proves that application attitude has a positive and significant influence on continued application use.